SIGNIFICANCE OF PLATELET INDICES IN PATIENTS WITH ACUTE ISCHEMIC STROKE (Iraqi Journal of Medical Sciences, 2016)
Background:Platelets play an important role in the development of intravascular thrombosis. Platelet size has been considered to reflect platelet activity. Platelet indices had been studied as an independent predictor of acute ischemic stroke (IS).Objectives:Assessing the relation of acute IS with different platelet indices.Methods:Fifty patients were enrolled: 25 of them had first acute IS (mean age 64 years, 12 (48%) were males) [group 1], while the rest 25 patients were those with more than one IS (mean age 68 years, 16 (64%) were males) [group 2] in comparison with the control group (20) subjects (mean age 57 years, 10 (50%) males). Work up included history and clinical examination in addition to brain CT scan and platelet indices which are: mean platelet count (MPC), mean platelet volume (MPV), platelet large cell ratio (P-LCR), and platelet distribution width (PDW) within first 24 hours of patient presentation.Results:The mean platelet count (MPC) was found to show significant difference between group 2 versus group 1 and control (P=0.012, P=0.023 respectively), while no statistically significant differences were reported with the other indices (MPV, PDW or P-LCR). Linear negative correlation was demonstrated between MPC and MPV, PDW and P-LCR in group 1, such correlation wasn't found in group 2.Conclusion:Mean platelet count (MPC) differs significantly in cases of multiple stokes in comparison with those having first stroke or the control group; therefore, the significance of this finding needs further studies.Keywords:Platelet indices, platelet count, mean platelet volume, platelet distribution width, platelet-large cell ratio, ischemic stroke.
Keywords: Platelet indices; platelet count; mean platelet volume; platelet distribution width; plateletlarge cell ratio; ischemic stroke